PENINGKATAN PEMAHAMAN MELALUI PEMBERDAYAAN PERAN TEMAN SEBAYA PADA PEMBELAJARAN IPA SISWA KELAS IX SMP NEGERI 38 SEMARANG - Masrikan Masrikan (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2015)
Results of observation found that the students of class IX and passive in learning science. Other facts indicate that the average student score of 60. This suggests that science teaching in class IX and unpleasant. In order to increase the students' understanding, then conducted action research.This study aims to determine students demonstrated the increased understanding of improving student learning outcomes IX class B SMP Negeri 38 Semarang through empowerment peers.The study design used two cycles with research time for 1 month. Subjects numbered 30 people.The first cycle study results showed an increased understanding marked by an increase in average student learning outcomes of 60 towards 71.6. Nevertheless, this study not yet may be terminated because it has not reached indicators of success that the average value of 75. The results of the second cycle studies show an increase in the average value becomes 75.8.This research recommendation is given to teachers IPA to further modify the model of science learning.